Peningkatan Hasil Belajar Jaring-jaring Bangun Ruang Menggunakan Model Project-Based Learning di Kelas V Sekolah Dasar - Zozeka, Arifantri; Masniladevi, Masniladevi (Universitas Negeri Padang, 2023)
This research is motivated by the low learning outcomes of students in class V SDN 01 Pauh, Padang City. This is because teachers have not used effective learning models in the learning process and teachers have also not taught students in project-based learning. This study aims to describe the increase in learning outcomes of simple geometric nets using the Project Based Learning (PjBL) model in class V SDN 01 Pauh, Padang City. This research is a classroom action research with qualitative and quantitative approaches. Implemented in 2 cycles, each cycle there are stages of planning, implementing, observing and reflecting. Observation, test, and non-test are the data collection techniques. The research subjects were teachers and students of class V SDN 01 Pauh. The results of the study show that the aspects observed have increased, namely: a) lesson plans in cycle I 91.66% (SB) cycle II 97.22% (SB), b) teacher activities in cycle I 89.06% (B) cycle II 96 .87% (SB), c) student activities cycle I 89.06% (B) cycle II 96.87% (SB), d) student learning outcomes cycle I 69.28 (C) cycle II 87.82 (b). It can be concluded that the Project Based Learning (PjBL) model can improve the learning outcomes of simple geometric nets in elementary schools.